1985
DOI: 10.1007/bf00348312
|View full text |Cite
|
Sign up to set email alerts
|

Non-linearities in the pharmacokinetics of di-(2-ethylhexyl) phthalate and metabolites in male rats

Abstract: The disposition of the plasticizer di-(2-ethylhexyl) phthalate (DEHP) and four of its major metabolites was studied in male rats given single infusions of a DEHP emulsion in doses of 5, 50 or 500 mg DEHP/kg body weight. Plasma concentrations of DEHP and metabolites were followed for 24 h after the start of the infusion. The kinetics of the primary metabolite mono-(2-ethylhexyl) phthalate (MEHP) was studied separately. The concentrations of DEHP in plasma were at all times considerably higher than those of MEHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In our study, the plasma testosterone concentration and relative weight of the seminal vesicle increased in the low-dose DEHP group and therefore the low-observed-effect level (LOEL) was 1.0 mg/kg, but Akingbemi et al 14) reported the LOEL of DEHP affecting steroidogenesis to be 10 mg/kg and the no-observed-effect level (NOEL) 1 mg/kg. Although there is no report about metabolites produced after inhalation of DEHP, higher concentrations of MEHHP and MEOHP were found in plasma following intravenous infusions of DEHP in rats 38) and the level of MEHP was lower after intravenous exposure than after oral 25-50% 0 (0%) 1 (17%) 1 (17%) 4 (marked) 50-75% 1 (17%) 0 (0%) 0 (0%) 5 (severe) > 75% 0 (0%) 0 (0%) 0 (0%) administration 21) . After inhalation of DEHP, the plasma concentrations of MEHHP and MEOHP may be higher than those after oral administration.…”
Section: Discussionmentioning
confidence: 91%
“…In our study, the plasma testosterone concentration and relative weight of the seminal vesicle increased in the low-dose DEHP group and therefore the low-observed-effect level (LOEL) was 1.0 mg/kg, but Akingbemi et al 14) reported the LOEL of DEHP affecting steroidogenesis to be 10 mg/kg and the no-observed-effect level (NOEL) 1 mg/kg. Although there is no report about metabolites produced after inhalation of DEHP, higher concentrations of MEHHP and MEOHP were found in plasma following intravenous infusions of DEHP in rats 38) and the level of MEHP was lower after intravenous exposure than after oral 25-50% 0 (0%) 1 (17%) 1 (17%) 4 (marked) 50-75% 1 (17%) 0 (0%) 0 (0%) 5 (severe) > 75% 0 (0%) 0 (0%) 0 (0%) administration 21) . After inhalation of DEHP, the plasma concentrations of MEHHP and MEOHP may be higher than those after oral administration.…”
Section: Discussionmentioning
confidence: 91%
“…Given single infusions of a DEHP emulsion in doses of 5, 50 or 500 mg/kg to rats, nonlinear increases in the AUCs of DEHP and MEHP indicated saturation in the formation as well as the elimination of the potentially toxic metabolite MEHP [31]. Testosterone production and gene endpoints in the fetal testis have been considered as the critical effect in some phthalate risk assessments, and thus the dose-response relationship for the effects of DEHP on the synthesis and production of testosterone in the fetal rat testis has been investigated [32].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies by Gray et al [21]on the addition of DEHP to liver and testicular cell culture indicate that DEHP has to be metabolized before it will exert any effect. Data obtained by several workers indicate that these metabolites of DEHP are responsible for the biological effects observed on administration of DEHP [22, 23]. Sjöberg et al [20]indicated that these metabolites, rather than DEHP itself, accumulate in the tissues.…”
Section: Discussionmentioning
confidence: 99%